Influencing Factors on Hospital Admissions among Chronic Obstructive Pulmonary Disease Patients in Qazvin Province - MohammadAli Zohal; Sima Rafiei; neda esmaeelzadeha; sanaz jamshidi; nafiseh rastgoo (Tehran University of Medical Sciences, 2020)
Background & Aim: Regarding the chronic course of obstructive pulmonary disease and multiple problems which it brings to individuals and the community in terms of physical, mental, and economic aspects; this study aimed to investigate the role of life-style factors in disease exacerbation and hospitalization among COPD patients. Methods & Materials: This is a descriptive, prospective study of outpatients with COPD in a tertiary care clinic. To collect data, a demographic questionnaire (including age, gender, marital status, occupation, and educational level), an international physical activity questionnaire (IPAQ), and a mini-nutritional assessment (MNA) tool were used. Disease severity was also determined by Initiative for Chronic Obstructive Lung Disease (GOLD) index. Results: A total of 128 patients (78.1% male) were recruited with a mean age of 65.3+11.9 years. Findings revealed significant correlations among physical activity level of patients and their nutrition, smoking behavior, BMI, and disease exacerbation. In fact patients with older age, lower BMI, smoking habit for a long time, and limited physical activity were more probable to face with disease exacerbation and hospitalization. Conclusion: Evidence suggests that adoption of health promotion strategies and emphasis on health based approaches can be helpful in reducing hospitalization among COPD patients. Due to their effectiveness and low cost, such policies are regarded as cost effective strategies in dealing with chronic diseases.